2020
DOI: 10.1093/trstmh/traa061
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes at 18 mo of 37 noma (cancrum oris) cases surgically treated at the Noma Children's Hospital, Sokoto, Nigeria

Abstract: Background Noma is a rapidly progressing infection of the oral cavity frequently resulting in severe facial disfigurement. We present a case series of noma patients surgically treated in northwest Nigeria. Methods A retrospective analysis of routinely collected data (demographics, diagnosis and surgical procedures undergone) and in-person follow-up assessments (anthropometry, mouth opening and quality of life measurements) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…These findings are mirrored in two Ethiopian studies 28,29 and a Nigerian study. 5 Our study has shown that the survivors of noma in Laos waited decades before being surgically treated, a finding similar to an Ethiopian study in which the median time from onset of symptoms to access to surgical care was 18 years. 28 These decades of suffering from facial disfigurement during childhood and adolescence frequently lead to stigma resulting in social isolation, excessive questions about the survivors' physical appearance, bullying, and selfconsciousness.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings are mirrored in two Ethiopian studies 28,29 and a Nigerian study. 5 Our study has shown that the survivors of noma in Laos waited decades before being surgically treated, a finding similar to an Ethiopian study in which the median time from onset of symptoms to access to surgical care was 18 years. 28 These decades of suffering from facial disfigurement during childhood and adolescence frequently lead to stigma resulting in social isolation, excessive questions about the survivors' physical appearance, bullying, and selfconsciousness.…”
Section: Discussionsupporting
confidence: 86%
“…4 Noma survivors suffer from functional and cosmetic problems, often leading to social exclusion and lack of opportunities from a young age. 3,5 Surgical rehabilitation for these patients is challenging, expensive, and often difficult to access or unavailable in endemic countries. 6 The majority of published literature on noma are case reports, case series, or retrospective studies, mostly from low-income countries in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The aesthetic and functional sequelae of noma are compounded by the psychological impacts of the disease, not only on the patient, but also on family members and caretakers. Studies have reported that noma has led to mental health issues due to the social isolation and shunning of survivors and their families, bullying, a lack of access to education, difficulties finding jobs, and limited marital prospects [ 16 , 102 , 141 , 156 , 163 , 169 – 172 ].…”
Section: Resultsmentioning
confidence: 99%
“…If the patient survives the acute illness, they can live into adulthood but often require extensive reconstructive surgery and intensive physiotherapy to improve the resulting structural and functional defects [ 174 ] that often require a number of surgical treatments [ 137 ]. Studies have highlighted the fact that the time between acute illness and surgical care can be decades [ 136 , 141 , 144 ]. The clinical manifestation of each noma case is unique, and as such, the surgical procedures used to treat each noma case differ [ 15 , 39 , 42 , 74 , 102 , 115 117 , 145 , 148 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation